2011
DOI: 10.2214/ajr.10.5698
|View full text |Cite
|
Sign up to set email alerts
|

Low-Kilovoltage, High-Tube-Current MDCT of Liver in Thin Adults: Pilot Study Evaluating Radiation Dose, Image Quality, and Display Settings

Abstract: At portal phase abdominal CT, 80 kVp and a high tube current-time product setting significantly improved image quality and reduced the radiation dose compared with 120 kVp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…Because low kVp DECT increases image noise, contrast enhancement, and soft tissue contrast, Nakaura et al hypothesized that wide window width display settings would improve the image quality of low kVp CT. Their results also suggest that wide window width display settings are optimal for the inspection of low kVp scans. A wider window width might reduce the contrast in qualitative analysis because it displays a larger CT number range [7]. Our data suggest that low kVp images require a lower window level and width to reach the highest conspicuity.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Because low kVp DECT increases image noise, contrast enhancement, and soft tissue contrast, Nakaura et al hypothesized that wide window width display settings would improve the image quality of low kVp CT. Their results also suggest that wide window width display settings are optimal for the inspection of low kVp scans. A wider window width might reduce the contrast in qualitative analysis because it displays a larger CT number range [7]. Our data suggest that low kVp images require a lower window level and width to reach the highest conspicuity.…”
Section: Discussionmentioning
confidence: 81%
“…Although a certain body circumference was regarded for the inclusion of patients, we did not consider this parameter in the statistical analysis. The most notable disadvantage of low-voltage CT is the potential for increased image noise (4,5,7,9,17) resulting from the lower tube energy, which results in unacceptable images in large patients. Beyond a certain patient size, the benefit of increased contrast and increased contrast-to-noise ratio (CNR) at 80 kV is offset by the increased noise and beam-hardening artifacts, thus making abdominal 80 kV single-source and dual-energy CT (using 80 kV in the lower energy tube) inadvisable [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The improved tagging efficiency at One major difference between this study and previous studies is that patients were not excluded on the basis of enlarged body habitus; however, multiple prior studies have indicated that lowering tube voltage leads to a disproportionate increase in image noise and a decrease in image quality in larger patients because of a decrease in photon penetration (24,39). However, this should make the current study more widely applicable to a Western population than prior studies, many of which were performed in thinner Asian populations (34,37).…”
Section: Qualitative 3d Image Analysismentioning
confidence: 92%
“…Other studies have examined the effect of a decrease in tube voltage on intravenous contrast-enhanced applications, such as CT angiography, indirect CT venography, CT perfusion, and routine abdominal CT, and have shown that a decrease in tube voltage, at least in thinner patients, leads to a significant decrease in radiation dose by 13%-57% (16,19,20,22,(34)(35)(36)(37).…”
Section: Qualitative 3d Image Analysismentioning
confidence: 99%
See 1 more Smart Citation